TELMISARTAN IN THE TREATMENT OF ARTERIAL HYPERTENSION. CASE STUDY - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Data on angiotensin II receptor blockers, one of the main drug classes used in cardiology , are presented. The advantages of this drugs class are highlighted with the focus on telmisartan. Additionally clinical example of successful telmisartan application in patients with hypertension, high risk of cardiovascular complications, and obesity is presented.